Industrial artificial granite and preparation method thereof
By synthesizing the copolymerization of functional monomers with flame retardant and antibacterial functions with vinyl unsaturated polyester resins, and producing hydrogen bonding with sepiolite powder and granite particles, artificial granite with excellent antibacterial and good flame retardant properties was prepared, which solved the problem of insufficient antibacterial and flame retardant properties of artificial granite in the prior art.
Patent Information
- Application Number
- CN202411727460.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The antibacterial and flame retardant properties of existing industrial artificial granite are insufficient, making it difficult to meet the demanding needs of industrial applications.
By synthesizing a functional monomer with both flame retardant and antibacterial copolymerization with unsaturated vinyl unsaturated polyester resin, and hydrogen bonding with sesapite powder and granite particles, artificial granite with excellent antibacterial and good flame retardant properties were prepared.
It achieves excellent antibacterial properties and good flame retardant properties of artificial granite, meets more demanding industrial application needs, and improves its application safety and heat resistance in humid and bacterial environments.
Smart Images

Figure BDA0005159539760000051 
Figure BDA0005159539760000061 
Figure BDA0005159539760000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, in particular to industrial artificial granite and a preparation method thereof. Background Art
[0002] Natural granite is widely used in building materials, machine tool base parts and other fields due to its hardness, wear resistance and high compressive strength. However, the mining and processing costs of natural granite are high, and the stone contains harmful radioactive elements, which limits its wide application. In order to solve these problems, researchers began to explore the preparation technology of artificial granite to replace natural granite and meet industrial needs. Artificial granite, also known as polymer concrete or epoxy granite, is an artificial granite material made of dense stacked rocks of various sizes, fillers and adhesives. It is not only suitable for conventional uses such as building exterior walls and floor paving, but can also be used in industrial fields such as machine tool base parts and measuring instrument bases. It has broad application prospects.
[0003] Industrial artificial granite is a high-quality building material and is widely used in the field of building decoration. However, the tiny pores on the surface of granite are easy to hide dirt and grime, and it is easy to breed bacteria and mold in a humid environment, which is harmful to people's health. In addition, the composition of artificial granite lacks substances with antibacterial activity, so its antibacterial performance is relatively weak. In the prior art, antibacterial agents are generally added by adding small molecule antibacterial agents such as nanosilver. However, the surface of granite is not easy to combine with the antibacterial agent, which makes it difficult for the antibacterial agent to form an effective antibacterial layer on the surface of the stone. In a humid and bacterial environment, the antibacterial performance of granite may further decrease, seriously affecting the expansion of its application range.
[0004] The flame retardant properties of industrial artificial granite are an issue that needs attention. The internal structure of artificial granite may have tiny pores and cracks. These defects may become channels for the spread of fire at high temperatures. When used in high-temperature or flammable environments such as industrial furnaces and combustion chambers, its flame retardant properties may not meet the requirements. In the prior art, the flame retardant properties of artificial granite are improved by adding inorganic flame retardants such as aluminum oxide and magnesium hydroxide. However, the flame retardant properties of such inorganic flame retardants are limited, and the dispersion in the granite matrix is poor and easy to agglomerate, which affects the further development of its flame retardant properties. The present invention aims to synthesize a functional monomer with both flame retardancy and antibacterial properties and copolymerize it with the unsaturated group of vinyl unsaturated polyester resin, and generate hydrogen bonds with sepiolite powder and granite particles, so that the prepared artificial granite meets more stringent industrial application requirements. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide an industrial artificial granite and a preparation method thereof, so as to overcome the problem that the artificial granite in the prior art has poor flame retardancy and antibacterial properties.
[0006] The present invention is achieved through the following technical solutions:
[0007] An industrial artificial granite comprises the following components in parts by weight: 100 parts of granite particles, 25-40 parts of aluminum hydroxide filler, 10-15 parts of aluminum silicate microbeads, 50-60 parts of vinyl unsaturated polyester resin, 5-25 parts of alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder, 2-5 parts of hardener, 1-3 parts of initiator, 0.8-1.5 parts of accelerator, 5-8 parts of masterbatch and 20-30 parts of deionized water.
[0008] The preparation method is carried out according to the following steps: adding granite particles, aluminum hydroxide filler and aluminum silicate microbeads into a high-powered mixer, stirring evenly, then adding alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder and deionized water, stirring for 5-10 minutes, adding vinyl unsaturated polyester resin and hardener, stirring at 35-50°C for 10-20 minutes, then adding initiator and accelerator and continuing to stir for 8-15 minutes, finally adding masterbatch for color adjustment, stirring evenly and then transferring to a mold, vacuum degassing for 40-60 minutes, placing on a hot press for curing and molding, cooling, cutting and polishing to obtain industrial artificial granite.
[0009] Furthermore, the average particle size of the aluminum hydroxide filler is 40-60 μm, and the average particle size of the aluminum silicate microbeads is 20-30 μm.
[0010] Furthermore, the hardener is tert-amyl peroxide-2-ethylhexyl carbonate, the initiator is cyclohexanone peroxide, and the accelerator is cobalt naphthenate.
[0011] Furthermore, the curing molding temperature is 95-110° C., the curing time is 1-3 hours, and the curing pressure is 10-20 MPa.
[0012] Further, the preparation method of the alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder is carried out according to the following steps:
[0013] Step (1), under a nitrogen atmosphere, add 4-vinylbenzaldehyde and 1,2-dichloroethane to a reaction flask, stir evenly, add N-[3-(trimethoxysilyl)propyl]aniline and sodium triacetoxyborohydride, react at 20-35° C. for 12-24 hours, adjust the pH to 8-9 with potassium hydroxide after quenching, wash with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain alkenyl tertiary amine siloxane.
[0014] Step (2), under a nitrogen atmosphere, add tri(2-chloroethyl) phosphate and acetonitrile to a reaction flask, stir evenly, add alkenyl tertiary amine siloxane, stir to react, after the reaction is completed, separate by column chromatography (methanol / dichloromethane=1:20), concentrate under reduced pressure, and dry to obtain alkenyl phosphorus nitrogen quaternary ammonium salt siloxane.
[0015] Step (3), add sepiolite powder and aqueous hydrochloric acid solution into a reaction flask and mix evenly, stir at 75-90° C. for 5-10 hours, filter with suction, then add alkenyl phosphorus nitrogen quaternary ammonium salt siloxane, react at 500-800 r / min and 90-110° C. for 3-5 hours, filter, wash with deionized water until neutral, dry and grind to obtain alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder.
[0016] Furthermore, in step (1), the ratio of 4-vinylbenzaldehyde, N-[3-(trimethoxysilyl)propyl]aniline and sodium triacetoxyborohydride is 1 mol:(1.05-1.2) mol:(1.35-1.6) mol.
[0017] Furthermore, in step (2), the ratio of tris(2-chloroethyl) phosphate to alkenyl tertiary amine siloxane is 1 mol:(3.1-3.3) mol.
[0018] Furthermore, in step (2), the reaction temperature is 65-80° C. and the reaction time is 8-16 h.
[0019] Furthermore, in step (3), the ratio of sepiolite powder, hydrochloric acid aqueous solution, and alkenylphosphorus nitrogen quaternary ammonium salt siloxane is 1 g: (10-15) mL: (1.2-1.5) g.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) Excellent antibacterial properties: The quaternary ammonium salt modified sepiolite powder contains quaternary ammonium salt components, which can be adsorbed onto the surface of bacteria or other microorganisms, penetrate the cell wall of microorganisms, and combine with the cell membrane of microorganisms, thereby changing the permeability of the cell membrane, causing metabolic disorders of bacterial cells and loss of key substances, and ultimately causing the death of bacteria, thereby achieving the purpose of antibacterial. The quaternary ammonium salt antibacterial component can be stably present in the granite matrix for a long time through chemical grafting, avoiding contamination by bacteria and other microorganisms, and has long-lasting antibacterial properties.
[0022] (2) Good flame retardant and heat resistant properties: Sepiolite powder itself contains non-halogen flame retardant elements such as magnesium and silicon, and has a fibrous structure that can inhibit the diffusion of oxygen, reduce thermal decomposition and volatilization, and form a protective layer to block the transfer of heat. Its layered silicate structure has a strong adsorption capacity and can adsorb free radicals and harmful gases generated during the combustion process, forming a physical barrier to reduce the rate and intensity of the combustion reaction; on the other hand, nitrogen, phosphorus, and silicon elements can produce a synergistic flame retardant effect. The carbon layer and protective layer formed after bonding with the sepiolite can block the transfer of oxygen and heat in multiple ways, thereby improving the flame retardant properties of granite. The modified sepiolite powder has good compatibility with granite particles, and the rigid benzene ring structure in its structure has good heat resistance. At the same time, sepiolite is a fibrous hydrous magnesium silicate clay mineral that can adhere to the surface of granite particles at high temperatures, maintain the stability of the structure, slow down the thermal aging degradation of the resin, and improve the heat resistance of the substrate.
[0023] (3) Excellent mechanical properties: A portion of the silicon-oxygen bonds on the surface of the alkenyl phosphorus nitrogen quaternary ammonium salt siloxane are hydrolyzed to form chemical bonds with the hydroxyl groups on the surface of the sepiolite powder. The other portion of the siloxane is hydrolyzed to form hydrogen bonds with granite particles, aluminum hydroxide fillers, etc., and initiates polymerization through the alkenyl group and unsaturated polyester, making the prepared granite structure dense. In addition, the carbon-carbon double bonds in its structure are opened to participate in the curing process, thereby improving its dispersion in the matrix filler and forming a dense cross-linked network structure, so that the mechanical properties of the artificial granite are significantly improved when subjected to bending stress and impact stress; at the same time, aluminum hydroxide fillers and aluminum silicate microbeads can be filled in the pores of brucite powder, increasing the density of the molecular structure of the artificial granite, thereby enhancing the strength of the artificial granite. DETAILED DESCRIPTION
[0024] The present invention is further described below by the description of specific embodiments, but it is not intended to limit the present invention. Those skilled in the art may make various modifications or improvements based on the basic idea of the present invention, but they are all within the scope of the present invention as long as they do not deviate from the basic idea of the present invention. Unless otherwise specified, the raw materials and reagents used in this application are all commercially available products or can be prepared by known methods.
[0025] Sepiolite powder (200 mesh): Xiangtan Yuanyuan Sepiolite Co., Ltd.
[0026] Vinyl unsaturated polyester resin: appearance is transparent light yellow liquid, acid value is 10 mgKOH / g, viscosity is 8 Pa·s (25°C), solid content is 67%, gel time is 8 min (25°C), produced by Jinling DSM Resins Co., Ltd.
[0027] Masterbatch: Brand No. 561521, produced by Golden Dot (Shenzhen) Industrial New Materials Co., Ltd.
[0028] 4-Vinylbenzaldehyde, CAS number is 1791-26-0.
[0029] N-[3-(Trimethoxysilyl)propyl]aniline, CAS number is 3068-76-6.
[0030] Tris(2-chloroethyl) phosphate, CAS number is 115-96-8.
[0031] Example 1
[0032] (1) Under nitrogen atmosphere, 55 mmol of 4-vinylbenzaldehyde and 220 mL of 1,2-dichloroethane were added to the reaction flask, and after stirring, 58.3 mmol of N-[3-(trimethoxysilyl)propyl]aniline and 81.4 mmol of sodium triacetoxyborohydride were added, and the mixture was reacted at 25°C for 16 h. After quenching with 0.1 mol / L hydrochloric acid solution, the pH was adjusted to 9 with 2 mol / L potassium hydroxide, and the mixture was washed with ethyl acetate and deionized water. The organic phase was concentrated and dried to obtain vinyl tertiary amine siloxane. The preparation reaction formula is as follows:
[0033]
[0034] (2) Under nitrogen atmosphere, 50 mmol of tris(2-chloroethyl) phosphate and 310 mL of acetonitrile were added to the reaction flask, stirred evenly, and then 160 mmol of alkenyl tertiary amine siloxane was added. The mixture was reacted at 75° C. for 12 h, separated by column chromatography (methanol / dichloromethane=1:20), concentrated under reduced pressure, and dried to obtain alkenyl phosphorus nitrogen quaternary ammonium salt siloxane. The preparation reaction formula is as follows:
[0035]
[0036] (3) Add 10 g of sepiolite powder and 120 mL of 1 mol / L hydrochloric acid aqueous solution into a reaction flask and mix well. Stir at 850° C. for 8 h, filter with suction, then add 12 g of alkenyl phosphorus nitrogen quaternary ammonium salt siloxane, react at 750 r / min and 105° C. for 4 h, filter, wash with deionized water until neutral, dry and grind to obtain alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder.
[0037] (4) Add 100 g of granite particles, 35 g of aluminum hydroxide filler and 12 aluminum silicate microbeads into a high-powered mixer and stir evenly. Then add 5 g of quaternary ammonium salt of alkenyl phosphorus nitrogen modified sepiolite powder and 25 g of deionized water and stir for 8 min. Then add 55 g of vinyl unsaturated polyester resin and 3 g of tert-amyl peroxide-2-ethylhexyl carbonate and stir at 40° C. for 15 min. Then add 2 g of cyclohexanone peroxide and 1.2 g of cobalt naphthenate and continue stirring for 12 min. Finally, add 7 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vacuum degassing for 50 min, place on a hot press, and perform curing molding at 105° C. and 15 MPa for 2 h. After cooling, cutting and polishing, industrial artificial granite is obtained.
[0038] Example 2
[0039] (1) Under nitrogen atmosphere, 120 mmol of 4-vinylbenzaldehyde and 360 mL of 1,2-dichloroethane were added to a reaction flask, and after stirring, 126 mmol of N-[3-(trimethoxysilyl)propyl]aniline and 162 mmol of sodium triacetoxyborohydride were added, and the mixture was reacted at 35° C. for 12 h. After quenching with 0.1 mol / L hydrochloric acid solution, the pH was adjusted to 8 with 2 mol / L potassium hydroxide, and the mixture was washed with ethyl acetate and deionized water. The organic phase was concentrated and dried to obtain vinyl tertiary amine siloxane.
[0040] (2) Under a nitrogen atmosphere, 110 mmol of tri(2-chloroethyl) phosphate and 550 mL of acetonitrile were added to a reaction flask, and after stirring, 341 mmol of alkenyl tertiary amine siloxane was added, and the mixture was reacted at 80° C. for 8 h. The mixture was separated by column chromatography (methanol / dichloromethane=1:20), concentrated under reduced pressure, and dried to obtain alkenyl phosphorus nitrogen quaternary ammonium salt siloxane.
[0041] (3) Add 10 g of sepiolite powder and 150 mL of 1 mol / L hydrochloric acid aqueous solution into a reaction flask and mix well. Stir at 90° C. for 5 h, filter with suction, then add 13 g of alkenyl phosphorus nitrogen quaternary ammonium salt siloxane, react at 800 r / min and 110° C. for 3 h, filter, wash with deionized water until neutral, dry and grind to obtain alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder.
[0042] (4) Add 100 g of granite particles, 25 g of aluminum hydroxide filler and 15 g of aluminum silicate microbeads into a high-powered mixer and stir evenly. Then add 10 g of quaternary ammonium salt of alkenyl phosphorus nitrogen modified sepiolite powder and 20 g of deionized water and stir for 5 min. Then add 50 g of vinyl unsaturated polyester resin and 2 g of tert-amyl peroxide-2-ethylhexyl carbonate and stir at 50° C. for 10 min. Then add 1 g of cyclohexanone peroxide and 0.8 g of cobalt naphthenate and continue stirring for 8 min. Finally, add 5 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vacuum degassing for 40 min, place on a hot press, and perform curing molding at 110° C. and 20 MPa for 1 h. After cooling, cutting and polishing, industrial artificial granite is obtained.
[0043] Example 3
[0044] (1) Under nitrogen atmosphere, 40 mmol of 4-vinylbenzaldehyde and 200 mL of 1,2-dichloroethane were added to a reaction flask, and after stirring, 48 mmol of N-[3-(trimethoxysilyl)propyl]aniline and 64 mmol of sodium triacetoxyborohydride were added, and the mixture was reacted at 20° C. for 24 h. After quenching with 0.1 mol / L hydrochloric acid solution, the pH was adjusted to 9 with 2 mol / L potassium hydroxide, and the mixture was washed with ethyl acetate and deionized water. The organic phase was concentrated and dried to obtain vinyl tertiary amine siloxane.
[0045] (2) Under a nitrogen atmosphere, 35 mmol of tri(2-chloroethyl) phosphate and 238 mL of acetonitrile were added to a reaction flask. After stirring, 112 mmol of alkenyl tertiary amine siloxane was added. The mixture was reacted at 65° C. for 16 h. The mixture was separated by column chromatography (methanol / dichloromethane=1:20), concentrated under reduced pressure, and dried to obtain alkenyl phosphorus nitrogen quaternary ammonium salt siloxane.
[0046] (3) Add 10 g of sepiolite powder and 150 mL of 1 mol / L hydrochloric acid aqueous solution into a reaction flask and mix well. Stir at 75 ° C for 10 h, filter with suction, then add 14 g of alkenyl phosphorus nitrogen quaternary ammonium salt siloxane, react at 500 r / min and 90 ° C for 5 h, filter, wash with deionized water until neutral, dry and grind to obtain alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder.
[0047] (4) Add 100 g of granite particles, 40 g of aluminum hydroxide filler and 10 g of aluminum silicate microbeads into a high-powered mixer and stir evenly. Then add 15 g of quaternary ammonium salt of alkenyl phosphorus nitrogen modified sepiolite powder and 30 g of deionized water and stir for 10 min. Then add 60 g of vinyl unsaturated polyester resin and 5 g of tert-amyl peroxide-2-ethylhexyl carbonate and stir at 35° C. for 20 min. Then add 3 g of cyclohexanone peroxide and 1.5 g of cobalt naphthenate and continue stirring for 15 min. Finally, add 8 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vacuum degassing for 60 min, place on a hot press, and perform curing molding at 95° C. and 10 MPa for 3 h. After cooling, cutting and polishing, industrial artificial granite is obtained.
[0048] Example 4
[0049] (1) Under nitrogen atmosphere, 62 mmol of 4-vinylbenzaldehyde and 280 mL of 1,2-dichloroethane were added to a reaction flask, and after stirring, 71.3 mmol of N-[3-(trimethoxysilyl)propyl]aniline and 89.9 mmol of sodium triacetoxyborohydride were added, and the mixture was reacted at 30° C. for 15 h. After quenching with 0.1 mol / L hydrochloric acid solution, the pH was adjusted to 8 with 2 mol / L potassium hydroxide, and the mixture was washed with ethyl acetate and deionized water. The organic phase was concentrated and dried to obtain vinyl tertiary amine siloxane.
[0050] (2) Under a nitrogen atmosphere, 45 mmol of tri(2-chloroethyl) phosphate and 275 mL of acetonitrile were added to a reaction flask. After stirring, 145 mmol of alkenyl tertiary amine siloxane was added. The mixture was reacted at 75° C. for 10 h. The mixture was separated by column chromatography (methanol / dichloromethane=1:20), concentrated under reduced pressure, and dried to obtain alkenyl phosphorus nitrogen quaternary ammonium salt siloxane.
[0051] (3) Add 10 g of sepiolite powder and 130 mL of 1 mol / L hydrochloric acid aqueous solution into a reaction flask and mix well. Stir at 85 ° C for 9 h, filter with suction, then add 15 g of alkenyl phosphorus nitrogen quaternary ammonium salt siloxane, react at 750 r / min and 105 ° C for 4 h, filter, wash with deionized water until neutral, dry and grind to obtain alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder.
[0052] (4) Add 100 g of granite particles, 32 g of aluminum hydroxide filler and 13 g of aluminum silicate microbeads into a high-powered mixer and stir evenly. Then add 20 g of quaternary ammonium salt of alkenyl phosphorus nitrogen modified sepiolite powder and 26 g of deionized water and stir for 8 min. Then add 52 g of vinyl unsaturated polyester resin and 3.5 g of tert-amyl peroxide-2-ethylhexyl carbonate and stir at 40° C. for 18 min. Then add 2.5 g of cyclohexanone peroxide and 1.2 g of cobalt naphthenate and continue stirring for 10 min. Finally, add 7 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vacuum degassing for 45 min, place on a hot press, and perform curing molding at 105° C. and 18 MPa for 2 h. After cooling, cutting and polishing, industrial artificial granite is obtained.
[0053] Example 5
[0054] (1) Under nitrogen atmosphere, 30 mmol of 4-vinylbenzaldehyde and 125 mL of 1,2-dichloroethane were added to a reaction flask, and after stirring, 33.6 mmol of N-[3-(trimethoxysilyl)propyl]aniline and 42 mmol of sodium triacetoxyborohydride were added, and the mixture was reacted at 35° C. for 24 h. After quenching with 0.1 mol / L hydrochloric acid solution, the pH was adjusted to 9 with 2 mol / L potassium hydroxide, and the mixture was washed with ethyl acetate and deionized water. The organic phase was concentrated and dried to obtain vinyl tertiary amine siloxane.
[0055] (2) Under a nitrogen atmosphere, 25 mmol of tri(2-chloroethyl) phosphate and 170 mL of acetonitrile were added to a reaction flask. After stirring, 78.8 mmol of alkenyl tertiary amine siloxane was added. The mixture was reacted at 75° C. for 12 h. The mixture was separated by column chromatography (methanol / dichloromethane=1:20), concentrated under reduced pressure, and dried to obtain alkenyl phosphorus nitrogen quaternary ammonium salt siloxane.
[0056] (3) Add 10 g of sepiolite powder and 145 mL of 1 mol / L hydrochloric acid aqueous solution into a reaction flask and mix well. Stir at 80° C. for 7 h, filter with suction, then add 15 g of alkenyl phosphorus nitrogen quaternary ammonium salt siloxane, react at 800 r / min and 100° C. for 5 h, filter, wash with deionized water until neutral, dry and grind to obtain alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder.
[0057] (4) Add 100 g of granite particles, 36 g of aluminum hydroxide filler and 14 g of aluminum silicate microbeads into a high-powered mixer and stir evenly. Then add 25 g of quaternary ammonium salt of alkenyl phosphorus nitrogen modified sepiolite powder and 28 g of deionized water and stir for 6 min. Then add 55 g of vinyl unsaturated polyester resin and 3 g of tert-amyl peroxide-2-ethylhexyl carbonate and stir at 45° C. for 14 min. Then add 2.5 g of cyclohexanone peroxide and 1 g of cobalt naphthenate and continue stirring for 12 min. Finally, add 7 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vacuum degassing for 45 min, place on a hot press, and perform curing molding at 110° C. and 12 MPa for 2 h. After cooling, cutting and polishing, industrial artificial granite is obtained.
[0058] Comparative Example 1
[0059] (1) Add 10 g of sepiolite powder and 120 mL of 1 mol / L hydrochloric acid aqueous solution into a reaction flask and mix well. Stir at 850° C. for 8 h, filter with suction, then add 12 g of alkenyl tertiary amine siloxane (prepared in Example 1), react at 750 r / min and 105° C. for 4 h, filter, wash with deionized water until neutral, dry and grind to obtain alkenylbenzene-modified sepiolite powder.
[0060] (2) Add 100 g of granite particles, 35 g of aluminum hydroxide filler and 12 aluminum silicate microbeads into a high-powered mixer and stir evenly. Then add 5 g of vinylbenzene-modified sepiolite powder and 25 g of deionized water and stir for 8 min. Then add 55 g of vinyl unsaturated polyester resin and 3 g of tert-amyl peroxide-2-ethylhexyl carbonate and stir at 40° C. for 15 min. Then add 2 g of cyclohexanone peroxide and 1.2 g of cobalt naphthenate and continue stirring for 12 min. Finally, add 7 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vacuum degassing for 50 min, place on a hot press, and solidify and mold at 105° C. and 15 MPa for 2 h. After cooling, cutting and polishing, industrial artificial granite is obtained.
[0061] Comparative Example 2
[0062] Add 100g of granite particles, 35g of aluminum hydroxide filler and 12 aluminum silicate microbeads into a high-powered mixer and stir evenly. Then add 5g of sepiolite powder and 25g of deionized water and stir for 8min. Add 55g of vinyl unsaturated polyester resin and 3g of peroxy-2-ethylhexyl carbonate tert-amyl ester and stir at 40°C for 15min. Then add 2g of cyclohexanone peroxide and 1.2g of cobalt cyclohexane acid and continue stirring for 12min. Finally, add 7g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vacuum degassing for 50min, place on a hot press, and solidify and mold at 105°C and 15MPa for 2h. After cooling, cutting and polishing, industrial artificial granite is obtained.
[0063] Antibacterial performance test: The test was conducted in accordance with the provisions of the building materials industry standard JC / T897-2002 "Antibacterial Performance of Antibacterial Ceramic Products". The film method was used, that is, a certain number of Escherichia coli and Staphylococcus aureus were inoculated on the prepared artificial granite, covered with plastic wrap, and cultured at 37°C for 24 hours. The number of colonies was observed and the antibacterial rate was calculated. The initial colony counts of Escherichia coli and Staphylococcus aureus were 1.9×10 5 CFU and 1.3 × 10 5 CFU.
[0064] Table 1 Antibacterial performance test
[0065]
[0066] As can be seen from the test results in the above table, granite without quaternary ammonium salt components has no antibacterial property, and with the increase of the content of alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder, the antibacterial property of artificial granite gradually increases, wherein the antibacterial rates of Escherichia coli and Staphylococcus aureus in Example 5 reach 99.9% and 96.0%, respectively, with good antibacterial property, because alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder contains quaternary ammonium salt components, which are adsorbed to the surface of bacteria or other microorganisms, penetrate the cell wall of microorganisms, and combine with the cell membrane of microorganisms, change the permeability of cell membranes, make bacterial cell metabolism disorder and key substances loss, and finally make the cell die, so as to achieve the purpose of antibacterial; quaternary ammonium salt antibacterial components are able to be stably present in the granite matrix for a long time through chemical grafting, avoid the contamination of microorganisms such as bacteria, and have antibacterial persistence. Comparative Examples 1 and 2 do not contain quaternary ammonium salt antibacterial components and have no antibacterial effect.
[0067] Flame retardant performance test: The ignition time and peak heat release rate of artificial granite were tested using a cone calorimeter. The prepared artificial granite was cut into a size of 100mm×100mm×5mm. The external radiation heat flux intensity was 50kW / m 2 , each sample was measured five times and the average value was taken.
[0068] Heat resistance test: Place an oil pan at a temperature of 250°C on the prepared artificial granite for 1 hour, and visually observe whether it changes color to test its heat resistance.
[0069] Table 2 Flame retardant and heat resistance test
[0070] Ignition time(s) Heat resistance Example 1 108 No color change Example 2 125 No color change Example 3 148 No color change Example 4 162 No color change Example 5 165 No color change Comparative Example 1 92 No color change Comparative Example 2 65 Obvious discoloration
[0071] Ignition time refers to the time from when the test sample is exposed to the heat radiation source to when the fire source is ignited with a certain standard under a certain heater heat flux radiation intensity until the continuous ignition phenomenon appears on the surface; from the test results in the above table, it can be seen that with the increase of the content of alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder, the ignition time of artificial granite is gradually prolonged, and it has good flame retardant properties. This is because on the one hand, the sepiolite powder itself contains non-halogen flame retardant elements such as magnesium and silicon, and has a fibrous structure, which can inhibit the diffusion of oxygen, reduce thermal decomposition and volatilization, and form a protective layer to block the transfer of heat. Its layered silicate structure has a strong adsorption capacity, which can adsorb free radicals and harmful gases generated during the combustion process, forming a physical barrier to reduce the rate and intensity of the combustion reaction; on the other hand, nitrogen, phosphorus and silicon elements can produce a synergistic flame retardant effect, and the carbon layer and protective layer formed after bonding with sepiolite can block the transfer of oxygen and heat in multiple ways, thereby improving the flame retardant properties of granite.
[0072] The modified sepiolite powder has good compatibility with granite particles, etc. The rigid benzene ring structure in its structure has good heat resistance. At the same time, sepiolite is a fibrous hydrous magnesium silicate clay mineral that can adhere to the surface of granite particles at high temperatures, maintain the stability of the structure, slow down the thermal aging degradation of the resin, and improve the heat resistance of the substrate. Comparative Example 1 does not contain nitrogen, phosphorus and silicon synergistic flame retardant elements, and has average flame retardant properties, but contains a rigid benzene ring structure and has good heat resistance; the sepiolite powder in Comparative Example 2 is not modified, and has poor flame retardant and heat resistance properties.
[0073] Impact strength test: Referring to GB / T2571-1995 standard, a simply supported beam pendulum impact tester is used to apply an impact bending load to the sample to destroy the sample and use the energy absorbed per unit area when the sample is destroyed to measure the impact toughness of the material. The sample size is 100mm×100mm×50mm.
[0074] Compressive strength test: The artificial granite was made into a sample with a size of 100 mm × 100 mm × 50 mm, and the compressive strength test was carried out using an electronic universal testing machine with a loading rate of 10 mm / min.
[0075] Table 3 Mechanical properties test
[0076] <![CDATA[Impact strength (kJ / m 2 )]]> Compressive strength(MPa) Example 1 4.59 95.3 Example 2 5.32 102.6 Example 3 5.83 114.8 Example 4 6.27 123.4 Example 5 6.45 125.0 Comparative Example 1 3.80 81.5 Comparative Example 2 2.56 73.2
[0077] A part of the silicon-oxygen bonds on the surface of the alkenyl phosphorus nitrogen quaternary ammonium salt siloxane are hydrolyzed to form chemical bonds with the hydroxyl groups on the surface of the sepiolite powder, and the other part of the siloxane is hydrolyzed to form hydrogen bonds with the granite particles, aluminum hydroxide fillers, etc., and initiates polymerization through the alkenyl group and the unsaturated polyester, so that the prepared granite structure is dense. In addition, the carbon-carbon double bonds in its structure are opened to participate in the curing process, improve its dispersion in the matrix filler, and form a dense cross-linked network structure, so that the mechanical properties of the artificial granite are significantly improved when subjected to bending stress and impact stress; at the same time, the aluminum hydroxide filler and the aluminum silicate microbeads can be filled in the pores of the brucite powder, which increases the density of the molecular structure of the artificial granite, thereby enhancing the strength of the artificial granite.
[0078] Obviously, the specific implementation of the present invention is not limited to the above-mentioned methods. As long as various non-substantial improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A method for preparing industrial artificial granite, characterized in that: The artificial granite comprises the following components in parts by weight: 100 parts of granite particles, 25-40 parts of aluminum hydroxide filler, 10-15 parts of aluminum silicate microbeads, 50-60 parts of vinyl unsaturated polyester resin, 5-25 parts of vinyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder, 2-5 parts of hardener, 1-3 parts of initiator, 0.8-1.5 parts of accelerator, 5-8 parts of masterbatch and 20-30 parts of deionized water; The preparation method is carried out according to the following steps: adding granite particles, aluminum hydroxide filler and aluminum silicate microbeads into a powerful mixer, stirring evenly, then adding alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder and deionized water, stirring for 5-10 minutes, adding vinyl unsaturated polyester resin and hardener, stirring at 35-50°C for 10-20 minutes, then adding initiator and accelerator and continuing to stir for 8-15 minutes, finally adding masterbatch for color adjustment, stirring evenly and transferring to a mold, vacuum degassing for 40-60 minutes, placing on a hot press for curing and molding, cooling, cutting and polishing to obtain industrial artificial granite.
2. The method for preparing industrial artificial granite according to claim 1, characterized in that: The average particle size of the aluminum hydroxide filler is 40-60 μm, and the average particle size of the aluminum silicate microbeads is 20-30 μm.
3. The method for preparing industrial artificial granite according to claim 1, characterized in that: The hardener is tert-amyl peroxide-2-ethylhexyl carbonate, the initiator is cyclohexanone peroxide, and the accelerator is cobalt naphthenate.
4. The method for preparing industrial artificial granite according to claim 1, characterized in that: The curing molding temperature is 95-110° C., the curing time is 1-3 hours, and the curing pressure is 10-20 MPa.
5. The method for preparing industrial artificial granite according to claim 1, characterized in that: The preparation method of the alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder is carried out according to the following steps: Step (1), under a nitrogen atmosphere, add 4-vinylbenzaldehyde and 1,2-dichloroethane to a reaction flask, stir evenly, add N-[3-(trimethoxysilyl)propyl]aniline and sodium triacetoxyborohydride, react at 20-35° C. for 12-24 hours, adjust the pH to 8-9 with potassium hydroxide after quenching, wash with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain alkenyl tertiary amine siloxane; Step (2), under a nitrogen atmosphere, add tri(2-chloroethyl) phosphate and acetonitrile to a reaction flask, stir evenly, add alkenyl tertiary amine siloxane, stir to react, after the reaction is completed, separate by column chromatography, concentrate under reduced pressure, and dry to obtain alkenyl phosphorus nitrogen quaternary ammonium salt siloxane; Step (3), add sepiolite powder and hydrochloric acid aqueous solution into a reaction flask and mix evenly, stir at 75-90° C. for 5-10 hours, filter with suction, then add alkenyl phosphorus nitrogen quaternary ammonium salt siloxane, react at 500-800 r / min and 90-110° C. for 3-5 hours, filter, wash with deionized water until neutral, dry and grind to obtain alkenyl phosphorus nitrogen quaternary ammonium salt modified sepiolite powder.
6. The method for preparing industrial artificial granite according to claim 5, characterized in that: In the step (1), the ratio of 4-vinylbenzaldehyde, N-[3-(trimethoxysilyl)propyl]aniline and sodium triacetoxyborohydride is 1 mol: (1.05-1.2) mol: (1.35-1.6) mol.
7. The method for preparing industrial artificial granite according to claim 5, characterized in that: In the step (2), the ratio of tri(2-chloroethyl) phosphate to alkenyl tertiary amine siloxane is 1 mol: (3.1-3.3) mol.
8. The method for preparing industrial artificial granite according to claim 5, characterized in that: In the step (2), the reaction temperature is 65-80° C. and the reaction time is 8-16 h.
9. The method for preparing industrial artificial granite according to claim 5, characterized in that: In the step (3), the ratio of sepiolite powder, hydrochloric acid aqueous solution, and alkenylphosphorus nitrogen quaternary ammonium salt siloxane is 1 g: (10-15) mL: (1.2-1.5) g.
10. An industrial artificial granite, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.